Person-environment fit: the Missing Link in the Organisational Culture -Commitment Relationship - Wee Yu Ghee; Kamarul Zaman Ahmad; Kayathry a/p Veerapandian (Canadian Center of Science and Education, 2011)
The purpose of this study was to investigate the mediating effect of person-environment fit on the relationship between organisational culture and organisational commitment. Data were obtained from full-time employees who were working in private and public sectors from various organisations in Malaysia (n = 204). Person-environment fit was found to be a significant mediator of the relationship between organisational culture and organisational commitment. This has wide-ranging implications for organisational development consultants who intend to shape the culture of various organisations, on the assumption that certain organisational cultures directly lead to certain desirable employee outcomes. Managers need to pay attention to not only their organisational culture such as training, rewards, teamwork and communication, but to also ensure that they are aimed towards improving the fit between individuals and their work environment. Whereas previous research tends to look at P-E fit as a predictor of employee outcomes, this is one of the first few studies to provide evidence of P-E fit as a mediator of the relationship between organisational culture and organisational commitment.